DEVELOPMENT AND LEVEL OF EFFICIENCY OF TRADE ACTIVITIES BY RETAIL ENTERPRISES OF UKRAINE - Коваль, Н. В.; Корженівська, Н. Л.; Добровольська, Е. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2020)
Development of trading activities is carried out in accordance with the current Concept of development of internal trade of Ukraine. At a rapid pace, changes are occurring in consumer preferences, assortment conditions, and the expansion of the influence of the geographical and species capabilities of the presented goods. The analysis of internal changes in the volume of goods turnover of enterprises by product groups, business entities at the country level and its individual regions made it possible to argue and justify the importance of observing the totality of organization principles, the balance of supply and demand, purchasing power, economic feasibility and payback. The used methods of author generalizations, analytical and statistical calculations, comparisons made it possible to systematize the digital material of the study and substantiate conclusions regarding the state and dynamics of the development of trade activities in Ukraine, as well as the Khmelnitsky region, as one of its regions. The study focuses on network marketing, as one of the forms of development and improvement of trade and the determination of the necessary nomenclature and bottlenecks in the activities of trade entities, including markets. The prospects of the use of electronic commerce (purchase and sales) are substantiated, which significantly expands the possibilities for carrying out trading activities for both buyers and trade enterprises. It is proposed to take into account the influence of demographic security, as one of the factors that shape the country’s product policy and its export potential. It is determined that the influence on the increase in turnover indicators has an extensive factor in the growth of prices for consumed goods, in a certain way introduces distortions in the perception of digital information. The use of innovative technologies, modern methods of managerial decision-making in the field of marketing, logistics allows us to improve the trading process, satisfy consumer demand and ensure the effectiveness of enterprises in the trading sphere.